2000
DOI: 10.1577/1548-8667(2000)012<0018:ppaumo>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Pfiesteria piscicidaand Ulcerative Mycosis of Atlantic Menhaden—Current Status of Understanding

Abstract: Ulcerative lesions in estuarine finfish are associated with a variety of parasitic, bacterial, and fungal infectious agents as well as water quality and other abiotic stress factors. Atlantic menhaden Brevoortia tyrannus are a severely affected species typically exhibiting solitary, perianal, focal, deep, granulomatous lesions containing oomycete hyphae. Intense recent emphasis in the scientific literature and in the popular press has been placed on Pfiesteria-like dinoflagellates and their toxins as the causa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…The relationship between Pfiesteria and fish lesions, however, was based on laboratory studies that did not simulate natural conditions. Those studies were challenged by a number of researchers (10,11,(41)(42)(43)(44), and there is now a large body of research evidence that supports the primary role of A. invadans in causing UM. Repeated histological surveys of UM-affected fish have found a high number of broad aseptate hyphae in the ulcers (2,4,12,13,24,25,35).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between Pfiesteria and fish lesions, however, was based on laboratory studies that did not simulate natural conditions. Those studies were challenged by a number of researchers (10,11,(41)(42)(43)(44), and there is now a large body of research evidence that supports the primary role of A. invadans in causing UM. Repeated histological surveys of UM-affected fish have found a high number of broad aseptate hyphae in the ulcers (2,4,12,13,24,25,35).…”
Section: Discussionmentioning
confidence: 99%
“…*Significantly different from control (p < 0.05) Aphanomyces to induce ulceration in fish (Dykstra et al 1989, Dykstra & Kane 2000, Kiryu et al 2003, Sosa et al 2007) but data regarding oxidant or antioxidant status in response to such fungal infections are not available in literature. The present study showed that LPO level in gills of fish exposed to the 2 infection agents was strongly increased but was not affected in muscles of fish compared with the control.…”
Section: Oxidative Stress Biomarkersmentioning
confidence: 99%
“…Also, some species of the genus Aphanomyces induce skin and muscle lesions termed ulcerative mycosis in fish from western Atlantic estuarine waters (Dykstra & Kane 2000). Most studies of the pathological effect of fungal infection on fish have not focused on studying the oxidant or antioxidant status.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of factors leading to skin damage appear to predispose fish to infection, including physical trauma (Kiryu et al, 2003), exposure to water of low pH (Bondad-Reantaso et al, 1992;Callinan et al, 1996;Fairweather, 1999;Choongo et al, 2009), skin lesions as a result of intra-species aggression (biting) (Fairweather, 1999;Saylor et al, 2010), or infections of fish with dinoflagellates (Dykstra and Kane, 2000). Challenge experiments with strains of A. invadans from Southeast Asia have suggested that zoospores attach to the dermis and not the epidermis before invasion .…”
Section: Predisposing Factors For Infection/factors Influencing Exprementioning
confidence: 99%
“…drop in water salinity, low alkalinity and high ammonia, general poor water quality, low oxygen levels) (Callinan et al, 1989;Virgona, 1992;Pathiratne et al, 1999;Mohan et al, 1999;. Further factors that have been associated with infection are exposure to toxins (Dykstra and Kane, 2000) and infection with ectoparasites, bacteria or viruses .…”
Section: Predisposing Factors For Infection/factors Influencing Exprementioning
confidence: 99%